Giant Cell Tumor of Talus – Role of imaging - Sharma, Bharat B; Sharma, Sandeep; Ramchandran, Priya; Maggu, NK; Kakar, Sameer; Govila, Vinay K (Indian Journal of Case Reports, 2016)
Giant cell tumor (GCT) or Osteoclastoma of the tarsal bone is very rare as compared to that of long bones. The involvement of talus becomes unique in its presentation as it remains undiagnosed for a long time. The tumor usually occurs in younger age especially in small bones of hands and feet. We present a case of 34-years old male who presented with sprain of left foot and was finally diagnosed as giant cell tumor of the talus. This was possible with the help of various radiological modalities like plain X-ray, computerised tomography (CT) and magnetic resonance imaging (MRI). GCT of talus may be found as an incidental finding but the subsequent management depends upon the staging of the tumor as per the radiological evaluation.